Long-Term Oncologic and Reproductive Outcomes in Young Women With Early Endometrial Cancer Conservatively Treated: A Prospective Study and Literature Update. Issue 9 (November 2016) - Laurelli, Giuseppe; Falcone, Francesca; Gallo, Maria Stella; Scala, Felice; Losito, Simona; Granata, Vincenza; Cascella, Marco; Greggi, Stefano
Abstract : Objective: This study aimed to analyze the long-term oncologic and reproductive outcomes in endometrial cancer (EC) in young patients conservatively treated by combined hysteroscopic resection (HR) and levonorgestrel intrauterine device (LNG-IUD). Methods: Twenty-one patients (age ⩽ 40 years; Stage IA, G1-2 endometrioid EC), wishing to preserve their fertility, were enrolled into this prospective study. The HR was used to resect (1) the tumor lesion, (2) the endometrium adjacent to the tumor, and (3) the myometrium underlying the tumor. Hormonal therapy consisted of LNG-IUD (52 mg) for at least 6 months. Results: The median follow-up time is 85 months (range, 30–114). After 3 months from the progestin start date, 18 patients (85.7%) showed a complete regression (CR), 2 (9.5%) showed persistent disease, whereas 1 patient (4.8%) presented with progressive disease and underwent definitive surgery (Stage IA, G3 endometrioid). At 6 months, 1 of the 2 persistences underwent definitive surgery (Stage IA, G1 endometrioid), whereas the other was successfully re-treated. Two recurrences (10.5%) were observed, both involving the endometrium and synchronous ovarian cancer (OC) (atypical hyperplasia and Stage IIB G1 endometrioid OC; Stage IA endometrioid G1 EC, and Stage IA G1 endometrioid OC). The median duration of complete response was 85 months (range, 8–117). Sixty-three percent of complete responders attempted to conceive with 92% and 83% pregnancy and live birth rates, respectively. To date, all patients are alive and have no evidence of disease. Conclusions: After a long follow-up, combined HR and LNG-IUD would seem to improve the efficacy of progestin alone. High pregnancy and live birth rates were observed in women attempting to conceive. This approach is still experimental and should be offered only in the framework of scientific protocols conducted in cancer centers.